Challenges in Diagnosis and Treatment of Male Hypogonadism - Dyah Purnamasari (Acta Medica Indonesiana)
Hypogonadism is a condition characterized by diminished or absent production of sex hormones by the testicles in men and the ovaries in women. Hypogonadism is classified into primary and secondary hypogonadism. Each type of hypogonadism can be caused by congenital and acquired factors. There are many factors that contribute to the occurrence of hypogonadism, including genetic and developmental disorders, infection, kidney disease, liver disease, autoimmune disorders, chemotherapy, radiation, surgery, and trauma. This represents the considerable challenge in diagnosing hypogonadism.